If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-7x + -8) + 3x = 184 Reorder the terms: 5(-8 + -7x) + 3x = 184 (-8 * 5 + -7x * 5) + 3x = 184 (-40 + -35x) + 3x = 184 Combine like terms: -35x + 3x = -32x -40 + -32x = 184 Solving -40 + -32x = 184 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + -32x = 184 + 40 Combine like terms: -40 + 40 = 0 0 + -32x = 184 + 40 -32x = 184 + 40 Combine like terms: 184 + 40 = 224 -32x = 224 Divide each side by '-32'. x = -7 Simplifying x = -7
| x-3x^(1/2)-18=0 | | 7z*2=9-3z | | 3cot^2x-6=0 | | 21x+28-2=10x+12 | | -x^3+20x+80=0 | | x-3x^(1/2)–18=0 | | 8x-32=14x-(2x+80) | | x+5+4x-60=90 | | 7.36x+16=54.1696+4x | | |1/3-2|=4 | | -z^3+20z+80=0 | | 6.7x+33.5=67 | | x-3x^(1/2)-2x^2–18=0 | | 4y-6=2y+y | | -6x-10y=5 | | X*9=36 | | .5x-5=0 | | (-x-2)*2= | | 4x-60-x+5=90 | | 6r^2-24=0 | | z^3-5z^2-16z=-80 | | 4x-60+x+5=180 | | -7/5x=28 | | (-x-2)= | | log(x^2)=8 | | 5-3(6-4x)=4+2(5x-3) | | 4x-60+x+5=90 | | (-x-2)2= | | z^3-5z^2+64=0 | | 9x+11=11x-1 | | -z^3+20z+80z=0 | | -5=8/u |